Evaluation of antimicrobial short sequence peptides derived from mackerel gill and intestine against gram-negative bacteria - Wonganu Benjamaporn; Paenthong Mathaphon; Roytrakul Sittiruk (E3S Web of Conferences)
Antimicrobial peptides (AMPs) are small peptides that play a crucial role in growth inhibiting of pathogenic microorganisms in many organisms including humans. Therefore, the study of those peptides is interesting in the applications in food and pharmaceutical industries. This research focuses on mackerel gills and intestines, which are low-value but protein-rich wastes from processing of mackerel. These wastes can be hydrolyzed to protein hydrolysate, which might contain several amino acids and bioactive peptides. From the previous results, the protein hydrolysate derived from mackerel gills and intestines wastes had inhibited the growth of gram-negative bacteria, Vibrio parahaemolyticus, Klebsiella pneumoniae, and Salmonella typhimurium. The objective of this research is to analyze and identify inhibitory mechanisms on the growth of salmonella when it was treated with small peptides by using Venn diagram and STITCH database. The obtained small peptides might affect the growth inhibitory activities, anticancer activity, gyrase activity, and anti-angiotensin activity. To increase antimicrobial activity of peptides, especially against Vibrio parahaemolyticus and Klebsiella pneumoniae, the model of peptides created from Pepwheel help predict for containing higher hydrophobicity and more symmetry in the helix structure might provide better antibacterial activity of the peptides.